1991
DOI: 10.1055/s-2007-1013930
|View full text |Cite
|
Sign up to set email alerts
|

Results of Surgical Treatment in Patients with Stage IIIB Non-Small-Cell Lung Cancer

Abstract: From 1973 to March 1989, surgical resection was performed in 83 stage IIIB non-small-cell lung cancer patients (81% of all admitted stage IIIB patients). There were 2 operative deaths (2.3%), and complete resection was accomplished in 33 patients. The five-year survival rate of the patients undergoing complete resection was 25%, whereas that of the incomplete resection group was nil (p less than 0.05). Among the 26 patients with invasion of mediastinal structures who underwent complete resection, 3 patients su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 1 publication
1
9
0
Order By: Relevance
“…2 The only 5-year survivors in this study were patients with tracheal invasion. Elsewhere,' 3 5-year survival in tracheal resection patients was reported to about 20%. NO-1 patients may be good candidates for primary surgery.…”
Section: Discussionmentioning
confidence: 99%
“…2 The only 5-year survivors in this study were patients with tracheal invasion. Elsewhere,' 3 5-year survival in tracheal resection patients was reported to about 20%. NO-1 patients may be good candidates for primary surgery.…”
Section: Discussionmentioning
confidence: 99%
“…T4 lesion was originally defined as an unresectable group of locally advanced lung cancer. However, we have proposed that stage IIIB patients should not be uniformly excluded from surgical candidates and that, taking histology in account, the patients should be evaluated an eligibility for complete resection [18]. In fact, there are many reports in the recent years concerning combined resections of carina, heart and great vessel, or vertebral body with moderately favorable outcomes by an aid of assistant devices during the operation.…”
Section: Surgery For T4 Nsclcmentioning
confidence: 99%
“…For aorta resection, left subclavian artery-descending aorta bypass using Anthrone tube, or left atrium-descending aorta bypass using bio-pump was used. Partial left atrium resection, was done by an aid of extracorporeal circulation [18].…”
Section: Surgery For T4 Nsclcmentioning
confidence: 99%
“…In many previous studies, survival extension was shown in a selected group of T4 NSCLC patients who had been operated on (Watanabe et al, 1991;Martini et al, 1994;Izbicki et al, 1995;Bernard et al, 2001;Osaki et al, 2003;Pitz et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…For example, whether the treatment is curative or palliative, T4 diagnosis, the state of lymph nodes, the pathological subgroup type of the tumor, the age at diagnosis, smoking status, co-morbidity, ECOG-PS (Eastern Cooperative Oncology Group Performance Status), and weight loss can all be factors that affect treatment results and survival rates (Watanabe et al, 1991;Martini et al, 1994;Izbicki et al 1995;Bernard et al, 2001;Osaki et al, 2003;Pitz et al, 2003;Gregory et al, 2012). Therefore it is important to identify the factors that affect overall survival (OS) rate and event free survival (EFS) rates for the selection of treatments and differentiation of patients in this heterogeneous group of LA-NSCLC (T4 N0-3 M0) cases.…”
Section: Introductionmentioning
confidence: 99%